2012
DOI: 10.1111/jce.12003
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Predictors for Acute and Mid‐Term Success of Cryoballoon Ablation of Atrial Fibrillation Using the 28 mm Balloon

Abstract: Anatomical variables preventing maximal heat transfer from the tissue to the CB could be identified as predictors for CB-PVI failure with the 28 mm balloon. These findings may be a step toward a more tailored ablation strategy based on individual anatomical variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 25 publications
0
48
1
3
Order By: Relevance
“…These characteristics can be used to predict in which patients the cryoballoon approach will be effective and are in keeping with recent publications exploring anatomical predictors for success of cryoballoon PVI for the treatment of AF [21][22][23][24].…”
Section: Discussionmentioning
confidence: 79%
“…These characteristics can be used to predict in which patients the cryoballoon approach will be effective and are in keeping with recent publications exploring anatomical predictors for success of cryoballoon PVI for the treatment of AF [21][22][23][24].…”
Section: Discussionmentioning
confidence: 79%
“…The more proximal isolation may lead to a lower incidence of ATs. However, it has been reported lower PV isolation success when using the 28 mm first generation CB in cases in which PVs anatomy may force the distal end of the balloon to be in contact with the PV and, thus, lead to a lack of cooling in that region [20]. In fact, non-transmural chronic lesions leading to a typical PV reconnection pattern after CB-1 PV isolation has been described [21].…”
Section: Discussionmentioning
confidence: 97%
“…Anatomical variables preventing maximal cryoenergy transfer have been identified as possible predictors for CB PV isolation failure [11,20]. Regarding ATs, Mikhaylov et al Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in recently published studies authors found that unusual PV anatomy (number of PVs, angle of PV direction, early PV branches) is associated with worse AF freedom. 28,29 Regular ATs, identified on event-recorder strips before ablation, have been found in association with ATs after ablation. Considering the design of our study, we are not able to describe the mechanisms of ATs registered before ablation.…”
Section: Predictors Of Atrial Tachycardias After Cryoballoon Pulmonarmentioning
confidence: 99%